Encapsulation of (─)-epigallocatechin-3-gallate (EGCG) in solid lipid nanoparticles for food applications. (March 2019) - Shtay, Rasha; Keppler, Julia K.; Schrader, Katrin; Schwarz, Karin
Abstract: A nanoparticlulate delivery system was prepared for developing a food grade carrier for the major bioactive constituent in green tea; (─)-epigallocatechingallate (EGCG), in order to protect it against degradation during storage and digestion under simulated gastrointestinal pH conditions. EGCG-loaded solid lipid nanoparticles (EGCG-SLNs) were produced by the hot homogenization method. The lipid matrix used in the production consisted of pure cocoa butter. A combination of sodium stearoyl-2-lactylate (SSL) and mono- and diglycerides (MDG) was applied as a surfactant blend. The nanoparticles loaded with different concentrations of EGCG had an average particle size in the range of 108–122 nm. A maximal encapsulation efficiency of 68.5% was obtained. The produced food grade SLNs successfully protected the encapsulated EGCG along the storage period as well as under the adverse conditions at neutral pH values. The developed system offers good potential for enriching food products with EGCG. Highlights: Solid lipid nanoparticles (SLNs) were made from cocoa butter and food-grade surfactant blend. The system was developed for introducing Epigallocatechin-3-gallate (EGCG) into food products. EGCG-loaded SLNs system significantly enhanced the stability of EGCG at pH 6.8. The encapsulation of EGCG did not affect the particle size characteristics of SLNs. A prolonged release of EGCG from SLNs during in-vitro tests was reached.